An scFv‐Based Impedimetric Immunosensor Using SPCE/AuNP for RBD of SARS‐CoV‐2 Detection. Issue 1 (2nd January 2023) - Fadhilah, Ghina Nur; Yusuf, Muhammad; Sari, Arum Kurnia; Tohari, Taufik Ramdani; Wiraswati, Hesti Lina; Ekawardhani, Savira; Faridah, Lia; Fauziah, Nisa; Anshori, Isa; Wahyuni Hartati, Yeni
Abstract: A single‐chain variable fragment (scFv) is an antibody fragment composed of VH and VL linked by a hydrophilic linker that can be designed according to the shape of the target molecule and synthesized in prokaryotic or eukaryotic cells via biotechnology engineering. This study developed an electrochemical immunosensor that detects the RBD of SARS‐CoV‐2 using a screen‐printed carbon electrode modified with gold nanoparticles, and scFv as a bioreceptor. Electrochemical impedance spectroscopy was employed to measure specific interactions of antigens with antibodies. The developed immunosensor had a limit of detection and a quantification limit of 4.86 ng mL −1 and 16.20 ng mL −1, respectively. The immunosensor was stable at room temperature for up to 30 days' storage. The immunosensor was assessed at biosafety level 3 using 33 nasopharyngeal swab specimens (clinical samples); the pieces of data were compared with quantitative Reverse Transcriptase‐PCR. The agreement of the data, the low detection limit achieved, the rapid analysis (30 min), the miniaturization, and the portability of the instrument combined with the easiness to use has the potential to become Point of Care (POC) for diagnosing the COVID‐19 disease. Abstract : An electrochemical immunosensor with a single‐chain variable fragment (scFv) as a bioreceptor has been developed to detect the RBD of SARS‐CoV‐2. Immunosensors show good results in detecting RBD of SARS‐CoV‐2 in clinical samples of the nasopharynx, have relatively long shelf‐life stability and have the potential to become a POC diagnostic of COVID‐19.